Compassion Fatigue in Junior High School Guidance and Counseling Teachers: A Qualitative Study of Self-Harm Case Companions - Santi Riksa Pratiwi; Margaretha Maria Shinta Pratiwi; Mulya Virgonita Iswindari Winta (Psikostudia : Jurnal Psikologi, 2025)
This study was motivated by the prevalence of self-harm among adolescents, which requires junior high school guidance and counseling (BK) teachers to provide intensive support. Such conditions have the potential to trigger compassion fatigue in BK teachers due to their deep empathetic involvement with students experiencing emotional crises. This study aimed to explore the experiences of compassion fatigue among BK teachers who have accompanied students engaging in self-harm. A qualitative approach with a phenomenological design was employed. Three junior high school BK teachers in Central Java were selected through purposive sampling. Data were collected via in-depth interviews and analyzed using thematic analysis. The study identified six main themes: feelings of frustration as BK teachers, emotional memories of students’ stories, increased sensitivity, anxiety, emotional exhaustion, and difficulties concentrating. These findings indicate that intense empathetic involvement may lead to significant psychological strain. Therefore, this study recommends systematic emotional support for BK teachers to prevent and manage compassion fatigue.Penelitian ini dilatarbelakangi oleh kasus self-harm pada remaja, yang menuntut guru bimbingan dan konseling (BK) tingkat SMP untuk memberikan pendampingan intensif. Kondisi ini berpotensi memunculkan compassion fatigue pada guru BK akibat keterlibatan empatik yang mendalam terhadap siswa yang mengalami krisis emosional. Penelitian ini bertujuan untuk memahami pengalaman compassion fatigue pada guru BK yang pernah mendampingi siswa dengan perilaku self-harm. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologis. Informan berjumlah tiga guru BK tingkat SMP di Jawa Tengah yang dipilih melalui teknik purposive sampling. Data dikumpulkan dengan wawancara mendalam dan dianalisis menggunakan analisis tematik. Hasil penelitian mengungkap enam tema utama: perasaan frustasi sebagai guru BK, ingatan emosional terhadap cerita siswa, meningkatnya sensitivitas, rasa cemas, kelelahan emosional, dan kesulitan berkonsentrasi. Temuan ini menunjukkan bahwa keterlibatan empatik yang intens dapat menimbulkan tekanan psikologis yang signifikan. Oleh karena itu, studi ini merekomendasikan adanya dukungan emosional yang sistematis bagi guru BK untuk mencegah dan mengelola compassion fatigue